(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
There is a strong correlation between behaviour and academic success. The behaviour of students, including their mindset, determination, and dedication to learning, greatly influences their academic success. Effective learning behaviour, including a strong interest, a track record of success, and a natural aptitude for learning, contributes to improved psychological well-being in the classroom and school environment. However, disruptive behaviour, such as bullying or talking during lectures, can significantly impact the entire classroom and impede academic progress. In relation to academic success, studies have been conducted on time management behaviour, but no significant relationship has been discovered. Academic performance can be influenced by various social factors, including social ties and peer effects. In general, various aspects of behaviour, such as learning behaviour, disruptive behaviour, and social factors, play a crucial role in determining academic success. This paper examines the theoretical perspective of the relationship between student behaviour and academic achievement. It draws on various literature sources that discuss the parameters associated with student behaviour and academic achievement.